Challenges of epidemics public communication to health policies in Argentina - Petracci, Mónica (2020)
The main objective of the article is to reflect on the communication of public health policies about epidemics in Argentina from the Health Communication perspective. The methodological design was based on the systematization and classification of social research findings about AIDS, Cholera, H1N1 fever and Dengue. The purpose is to develop the outlines of a research and communication framework designed to strengthen the skills to cope with the challenge of public communication on epidemics in the contemporary society.